Pengaruh Saat Pemberian Pupuk Kandang dan Pupuk Anorganik Terhadap Pertumbuhan Wijen di Lahan Pasir Pantai - Nurhayati, Dewi Ratna; Prapto, Y.; Taryono, Taryono; Hanudin, Eko (Universitas Sebelas Maret (UNS), 2015)
Coastal sandy land as one of marginal land which potential become to be a sustainable productive land. Annual crops such as Sesame cultivation proper to developed as an agribusiness crops in coastal sandy land by chicken manure, or organic fertilizer and in organic fertilizer through the combination treatment of manure and inorganic proportionately. This study aimed to determine the best of time for fertilize on growth and yield of Sesame (Sesamum indicum L). This study conducted in Keburuhan, Purworejo, Coastal sandy land, Gadjah Mada's Agricultural station laboratory, from May until November 2014. This study used a factorial experiment Randomized Block Design (RBD) with four replications. Experiment arranged in with two-factor. First factor is the kind of variety: Sumberrejo-1, Sumberrejo-2. The second factor is, time of fertilize by chicken manure 11,25 tonnes/ha (75% of farmers recommendation)+inorganic fertilizers (N, P, K deficiency replacement dose equivalent to 18,75 tonnes/ha of chicken manure. Variable observed were: plant height, days to flowering, number of branch, root volume. The data analyzed by using analysis of variance at 5% level significance. The results showed that fastest flowering (45 days) was on the control treatmentin Sumberrejo-1. Keywords: coastal sandy land, organic fertilizer, in organic, Sumberrejo-1, Sumberrejo-2 Sesame (Sesamum indicum L.)